Insulin receptor cleavage induced by estrogen impairs insulin signaling. Issue 2 (30th December 2021) - Yuasa, Tomoyuki; Takata, Yasunori; Aki, Nanako; Kunimi, Kotaro; Satoh, Miki; Nii, Mari; Izumi, Yoshihiko; Otoda, Toshiki; Hashida, Seiichi; Osawa, Haruhiko; Aihara, Ken-ichi
Abstract : Introduction: Soluble insulin receptor (sIR), which is the ectodomain of insulin receptor (IR), is present in human plasma. Plasma sIR levels are positively correlated with blood glucose levels and negatively correlated with insulin sensitivity. An in vitro model of IR cleavage shows that extracellular calpain 2 directly cleaves IR, which generates sIR, and sequential cleavage of the IRβ subunit by γ-secretase impairs insulin signaling in a glucose concentration-dependent manner. Nevertheless, sIR levels vary among subjects with normal glucose levels. Research design and methods: We examined sIR levels of pregnant women throughout gestation. Using an in vitro model, we also investigated the molecular mechanisms of IR cleavage induced by estradiol. Results: In pregnant women, sIR levels were positively correlated with estrogen levels and significantly increased at late pregnancy independent of glucose levels. Using an in vitro model, estrogen elicited IR cleavage and impaired cellular insulin signaling. Estradiol-induced IR cleavage was inhibited by targeting of calpain 2 and γ-secretase. Estrogen exerted these biological effects via G protein-coupled estrogen receptor, and its selective ligand upregulated calpain 2 expression and promoted exosome secretion, which significantly increased extracellular calpain 2. Simultaneous stimulation of estrogen and high glucose levels had a synergic effect on IR cleavage. Metformin prevented calpain 2 release in exosomes and restored insulin signaling impaired by estrogen. Conclusions: Estradiol-induced IR cleavage causes cellular insulin resistance, and its molecular mechanisms are shared with those by high glucose levels. sIR levels at late pregnancy are significantly elevated along with estrogen levels. Therefore, estradiol-induced IR cleavage is preserved in pregnant women and could be part of the etiology of insulin resistance in gestational diabetes mellitus and overt diabetes during pregnancy.